Fostering Mathematical Creativity - Young, Julie (Learning to Teach Language Arts, Mathematics, Science, and Social Studies Through Research and Practice, 2021)
The world needs creative problem solvers, perhaps now more than ever. The mathematics classroom is the perfect place to cultivate such creative thinkers. Mathematics is often considered a rule-based subject that has little room for creativity. This manuscript aims to show that creativity has a place in the mathematics classroom. Teacher choices have a significant impact on whether creativity is fostered or suppressed in the math classroom. Through critical reflection of current teaching methods, teachers can create a classroom environment where creativity flourishes. Methods for doing so are discussed, including teaching for understanding, choosing and creating rich tasks that have a “lower floor and higher ceiling,” (Boaler, 2016) allowing ample time for thinking, and telling students to be creative.